Tourism-related department coordination during crisis: a policy network perspective - Yu, M.; Cheng, Mingming; Yu, Z. (2025)
This study examines the characteristics and structural effects of policy network within tourism and other related national departments during public health crises in China. We explore the role of the tourism department in the inter-organisational policy coordination. Using social network analysis and exponential random graph models (ERGM), this study reveals that the policy network is decentralised and incompact, with certain departments acting as intermediaries. However, the tourism department does not play a central role, coordinating reactively rather than serving as a key intermediary. This study advances the tourism literature by unveiling the structure of tourism-related policy network and identifying the role of the tourism department in the network. The study also contributes to policy network literature by proposing a policy network model with distinct structural properties, termed as ‘multi-intermediary connected network’. This model offers a robust theoretical framework for understanding policy coordination in crisis management, with broad implications beyond public health crises in tourism.